Security information and event management (SIEM) implementation - (Martin Stuart); Miller, David, 1959 November 5- (New York McGraw-Hill, 2011)
"Effectively manage the security information and events produced by your network with help from this authoritative guide. Written by IT security experts, Security Information and Event Management (SIEM) Implementation shows you how to deploy SIEM technologies to monitor, identify, document, and respond to security threats and reduce false-positive alerts. The book explains how to implement SIEM products from different vendors, and discusses the strengths, weaknesses, and advanced tuning of these systems. You'll also learn how to use SIEM capabilities for business intelligence. Real-world case studies are included in this comprehensive resource"-- |c Provided by publisher.
Includes index
Keywords: Computer networks -- Security measures; Computers -- Access control; Application logging (Computer science); Tin học